National Seminar on Novel Microbial Technologies for Sustainable Development - Dr. HITENDRA KUMAR PATEL, Guest Editor (International Journal of Life Science and Pharma Research, 2019)
Type 2 diabetes mellitus is a multifactorial diseasewhich is influenced by genetic and environmental factors. The prevalence of diabetes has increased overtime because of over nutrition and reduced physical activity. INSR is the member of the receptor tyrosine kinase family of proteins located on the chromosome 19 in Homosapiens. Insulin resistance is proposed as a key pathophysiological feature of polycystic ovary syndrome (PCOS) contributing to both reproductive and metabolic disturbances. Reproductively, insulin resistance increases hyperandrogenism through insulin increasing ovarian androgen production. Populations with prevalent insulin resistance are known to be at increased risk for Impaired Glucose Tolerance, Type 2 Diabetes mellitus and Cardio vascular disease. The main aim of this study is to investigate the association between INSR gene polymorphism and Type 2 diabetes mellitus in healthy and PCOS Patients. Values for various biochemical parameters such as age, hip or waist ratio, fasting insulin, LDL, HDL cholesterol levels etc for both healthy and PCOS patients were analyzed. Type 2 diabetes mellitus is screened by using the primer Exon8(A>G)T and INSR gene was restricted by using restriction enzyme NsiI that resulted in band pattern 239bp and 285bp by PCR -RFLP techniques.